Bilateral giant inguinoscrotal hernia. Presentation of a novel combined two-stage repair approach. Issue 3 (6th March 2020) - Menenakos, Charalambos; Albrecht, Hendrik C; Gretschel, Stephan
Abstract: Giant inguinoscrotal hernia is typically defined as hernia extending below the midpoint of the inner thigh, in the standing position. These hernias can be a demanding surgical problem as replacing bowel contents into the abdomen that can cause a life-threatening increase in intra-abdominal pressures. Various techniques such as preoperative progressive pneumoperitoneum (PPP), debulking of abdominal contents with visceral resections with or without omentectomy and phrenectomy have been suggested. We report the case of a 65-year-old patient with giant bilateral inguinal hernia. We applied a novel two-stage combined approach consisting of PPP with simultaneous single shot injection of botulinum toxin Type A into the anterior abdominal wall, and a second stage laparotomy with hernia repair (Stoppa technique). This technique makes possible the successful treatment of giant inguinal hernias without the need for visceral resection. To our knowledge, this is the first presented case of this combined treatment modality.